Development and application of an algorithmic-parametric tool to assess the contribution of urban forestry to mitigate floods. (September 2022) - Martins, Iago Longue; Lyra, Ana Paula
As an impact of climate change, water-related disasters, such as floods, are becoming more frequent. In this context, there is an increasing demand to improve the resiliency of urban settlements, using multiple approaches and techniques. This paper assesses one of those techniques, by developing an algorithmic-parametric tool to quantify how urban forestry reduces flood impacts from rainfall runoff. The assessment was comprised by three main methodological steps: (#1) observing the scientific literature on "the sponge effect" observed in green infrastructures; (#2) developing an algorithmic-parametric tool using the Grasshopper application to estimate rainfall runoff, considering the influence of urban forestry design factors; and (#3) performing digital simulations with this parametric tool using a Rhinoceros-Grasshopper interface. Results indicate this method is effective in assessing the efficacy of green interventions to mitigate urban flood damage and also in foreseeing how different design strategies impact urban hydrological dynamics.